Number Board Media to Stimulate the Symbolic Thinking Ability of Children Aged 5-6 Years - Saripah, Ipah; Tabroni, Imam; Wang, Yuanyuan; Zou, Guijiao (Yayasan Adra Karima Hubbi, 2023)
Children will experience a golden period that is very important and should not be missed until they are 3 years old. Because during these times, children's cognitive abilities are still growing and developing rapidly. In fact, about 80% of children's cognitive skills are optimized in the first 3 years of life, and up to 90% of their abilities will continue to develop until they reach the age of 5. Media is a tool that can be used as an intermediary in stimulating all aspects of development in early childhood both aspects of moral and religious values, physical motor aspects, language aspects, social emotional aspects and cognitive aspects. To stimulate all aspects of early childhood development cannot be separated from learning media because for early childhood learning is done through play using learning media both real media, audio media, visual media, environmental media and audio-visual media, so that learning activities in early childhood run effectively. This article will discuss how the influence of number board media in stimulating the symbolic thinking ability of children aged 5-6 years in Sumurugul Village.